Discovering Techplomacy : A Comparative Study of Denmark and France - Addae, Nana (2022)
In this thesis, the discourse of Denmark and France technology ambassador offices are examined and placed in the context of the broader diplomatic practices and strategic objectives of their respective countries. The dominant International Relations paradigms of realism, liberalism, and conservatism provide the foundations to draw similarities and differences between the techplomacy approaches of Denmark and France.